Integrating Art and Animation in Teaching Computer Programming for High School Students Experimental Study - Jawad, Hadeel Mohammed; Tout, Samir; Abualkibash, Munther; Xie, Yichun (IEEE International Conference on Electro Information Technology, 2018)
This paper discusses the results of an experimental study that was conducted to explore the effect of integrating art and animation in teaching computer programming on high school students' interest and knowledge in programming. The study aimed to explore the students' interest in pursuing a degree in Computer Science (CS) after graduation. Three groups of high school students were targeted with educational programming sessions, and the study variables were measured through pre and posttest surveys. A new web-based programming tool was developed and used as the treatment in this study. The developed tool includes the use of art, animation and code sharing to increase students' motivation in learning computer programming. The results of the study showed that the use of art, animation and code sharing increased students' knowledge, enjoyment, and motivation in learning computer programming, and hence, increased their interest in pursuing a degree in CS after graduation.